2014
DOI: 10.4161/viru.29234
|View full text |Cite
|
Sign up to set email alerts
|

Reduced virulence of melanizedCryptococcus neoformansinGalleria mellonella

Abstract: Fungal melanins are important in the virulence of many pathogenic fungi. In this study, we examined the role of melanin in the interaction between Cryptococcus neoformans and the invertebrate host, Galleria mellonella. C. neoformans was able to melanize in the presence of G. mellonella homogenate, indicating the presence of melanin substrates. Melanization was confirmed by the recovery of acid-resistant particles that were recognized by anti-melanin antibodies. In addition, we tested the effect of fungal melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…For C. neoformans, killing of larvae was shown to be more severe at 37 C, and melanization of yeast cells, morphology of the capsule and lytic activity of the haemolymph influence virulence potential and outcome. Furthermore, changes in capsule structure were observed in strains after several passages through Galleria mellonella, similar to what was shown for mammalian models (Mylonakis et al 2005;Eisenman et al 2014;Desalermos et al 2015;Trevijano-Contador et al 2015). For C. gattii it was demonstrated that major molecular types exhibit a range of virulence potential, with some strains having the potential to be more virulent than others.…”
Section: Virulence Traits Of Cryptococcus Neoformans and Cryptococcussupporting
confidence: 63%
“…For C. neoformans, killing of larvae was shown to be more severe at 37 C, and melanization of yeast cells, morphology of the capsule and lytic activity of the haemolymph influence virulence potential and outcome. Furthermore, changes in capsule structure were observed in strains after several passages through Galleria mellonella, similar to what was shown for mammalian models (Mylonakis et al 2005;Eisenman et al 2014;Desalermos et al 2015;Trevijano-Contador et al 2015). For C. gattii it was demonstrated that major molecular types exhibit a range of virulence potential, with some strains having the potential to be more virulent than others.…”
Section: Virulence Traits Of Cryptococcus Neoformans and Cryptococcussupporting
confidence: 63%
“…At the moment, it cannot be discarded that other factors play a role in this phenomenon. For example, C. neoformans can melanize when incubated in G. mellonella homogenates, 60 so maybe the fungus has the ability to act as a scavenger of melanin precursors from the hemolymph. When G. mellonella is infected by Beauveria bassiana, some strains also fail to induce larval melanization and in this case, this effect correlates with the production of toxins by the fungus.…”
Section: Discussionmentioning
confidence: 99%
“…A further challenge was to demonstrate if sublethal incubation times of NCT in vitro had an influence on the virulence of Scedosporium in an in vivo model. The virulence of Aspergillus and yeasts in the G. mellonella model was shown previously (32,(44)(45)(46), so we chose it as a practicable one. The model turned out to be suitable for S. apiospermum (IHEM 21170) and S. boydii, and a loss of virulence could be proved unambiguously after incubation in sublethal concentrations of NCT for 30 min.…”
Section: Discussionmentioning
confidence: 99%